Analisa Tingkat Kelelahan Lansia Post Covid-19 di Kota Pekanbaru - Hamid, Abdurrahman; Wisanti, Eka; Ezdha, Awaliyah Ulfah Ayudytha (Sekolah Tinggi Ilmu Kesehatan RS Husada, 2023)
Introduction: Long covid is a term used to describe an illness experienced by survivors of Covid-19 where they still feel the long-term effects of the Coronavirus much longer than expected. long covid symptoms are easy fatigue, shortness of breath, sore throat, cough, chest pain, joints, difficulty concentrating and problems with memory or brain fog, insomnia. Fatigue is the most common symptom experienced by elderly survivors of covid 19 after fever and shortness of breath which occurs in 30% of all elderly survivors of covid 19. Objective: The purpose of this research is to determine the level of fatigue of elderly survivors of covid 19 which will be associated with characteristics including the level of symptoms experienced. felt by the elderly. Methods: The methodology used is simple and descriptive so that it can see the level of fatigue of the elderly survivors of Covid 19 in the Pekanbaru city. The sample used was 40 elderly people at least 14 days after Covid 19 and showed negative test results. Result: The results of this study were no fatigue for 6 people (15%), mild fatigue for 22 people (55%), moderate fatigue for 10 people (25%), and very fatigue for 2 people (5%). Conclusion: health workers who treat COVID-19 patients, especially the elderly, can anticipate the impact, especially fatigue, by conducting an assessment after completing isolation so that later they can carry out appropriate nursing interventions.